Ukrainian IT Project Manager's Career Transitions to the First Job - Чайка, Ростислав (Київський національний університет імені Тараса Шевченка, 2023)
The article is devoted to the analysis of career transitions to the first place of work among Ukrainian IT project managers.Background. Software development is an increasingly important branch of the Ukrainian economy, especially in the period of rebalancing caused by the war and the flow of human talent from traditional economy sectors to new creative industries. Career transition to the project manager position is one of the easiest ways to attract personnel from other sectors of the economy to the IT industry. In this regard, it seems important to determine which socio-psychological factors contribute to the career transition of project managers in IT to the first place of work and to provide recommendations regarding measures to increase the number of IT specialists in Ukraine.Methods. A career and organizational psychology literature review was carried out on career transitions, career stages, and career choice. Analysis and synthesis were used to identify the methodological foundations of this psychological phenomenon. An online survey was conducted and an analysis of the sources of transitions to the first place of work in IT by project managers was presented. The method of transition to the first place of work is analyzed.Results. The concept of career transitions and related terms are revealed. The hypothesis about the predominance of the desired psychological portrait over the necessary knowledge when hiring project managers without experience in IT for the first place of work was confirmed. Based on the results of the research analysis, it is shown that the majority of transitions (53 %) to the position of the project manager are now taking place from within the IT industry due to self-study (79 %).Conclusion. The main factors that will contribute to a greater number of career transitions to the first position of non-IT project managers are determined to decrease the contrast between the position of an IT project manager and the position of a project manager from other areas of business. And also the minimization of negative surprises that can lead to the dismissal of such sweaters during the first employment. The expediency of introducing a greater number of activities to gain experience in project management, leadership, working communication, and creating and managing projects in university programs is indicated. Recommendations are provided for the following researchers and practitioners of project management who will work with the topic of career transitions to the first place of work of IT project managers in Ukraine.

Вступ. Розроблення програмного забезпечення - дедалі більш важлива галузь української економіки, особливо в період перебалансування, викликаного війною, та перетікання людських талантів із традиційних галузей економіки в нові креативні індустрії. Кар'єрний перехід на посаду проєктного менеджера - один із найпростіших способів залучити в IT-індустрію персонал з інших секторів економіки. У зв'язку з цим досліджено, які соціально-психологічні чинники сприяють кар'єрним переходам проєктних менеджерів в IT на перше місце праці та надано рекомендації щодо заходів зі збільшення кількості IT-спеціалістів в Україні.Методи. Здійснено огляд літератури з кар'єрної та організаційної психології про кар'єрні переходи, кар'єрні стадії і кар'єрний вибір. Використано аналіз та синтез для виокремлення методологічних засад цього психологічного явища. Проведено онлайн-опитування і презентовано аналіз джерел переходів на перше місце праці в IT проєктними менеджерами. Проаналізовано спосіб переходу на перше місце праці.Результати. Розкрито поняття кар'єрних переходів і пов'язаних з цим поняттям термінів. Підтверджено гіпотезу про переважання бажаного психологічного портрета над потрібними знаннями під час найму проєктних менеджерів без досвіду роботи в IT на перше місце праці. За результатами аналізу досліджень показано, що більшість переходів (53 %) на посаду проєктного менеджера зараз відбуваються зсередини IT-індустрїїзавдяки самостійному навчанню(79 %).Висновки. Виявлено, що серед основних чинників, які сприятимуть більшій кількості кар'єрних переходів на першу посаду проєктних менеджерів не з IT, є зменшення контрасту між посадою IT-проєктного менеджера та посадою проєктно- го менеджера з інших сфер бізнесу, а також мінімізація негативних сюрпризів, котрі можуть призвести до звільнень таких світчерів у разі першого працевлаштування. Зазначено доцільність введення в університетські програми більшої кількості заходів з отримання досвіду з управління проєктами, лідерства, робочого спілкування, створення і управління проєктами. Надано рекомендації для наступних дослідників та практиків проєктного менеджменту, котрі будуть працювати з темою кар'єрних переходів на перше місце праці IT-проєктних менеджерів в Україні.
Дослідження кар'єрних переходів українських IT-проєктних менеджерів на перше місце роботи
Keywords: кар’єрні переходи; кар’єрна психологія; професійна поведінка; кар’єрний вибір; психологія розвитку; зміна місця праці; career transitions; career psychology; vocational behavior; career decision-making; developmental psychology; job change